Changes in soil heterotrophic respiration, carbon availability, and microbial function in seven forests along a climate gradient. Issue 6 (21st August 2014) - Fang, Huajun; Cheng, Shulan; Wang, Yongsheng; Yu, Guirui; Xu, Minjie; Dang, Xusheng; Li, Linsen; Wang, Lei
Abstract: Soil microbial communities play an essential role in soil carbon (C) emission and C sequestration in forest ecosystems. However, little information is available regarding the relationship between soil C dynamics and microbial substrate utilization at large scales. Along the North–South Transect of Eastern China (NSTEC), seven forests representative of boreal, temperate and tropical biomes were examined. Soil heterotrophic respiration (Rh ), soil dissolved organic C (DOC), microbial biomass C (MBC), and microbial community‐level physiological profiles (CLPPs) were investigated using biochemical measurements, static chamber‐gas chromatography analysis, and Biolog‐Eco microplates, respectively. We found that soil Rh rates were significantly higher in subtropical and boreal forests than in temperate forests. Conversely, the concentrations of soil DOC and MBC, as well as microbial metabolic activity and functional diversity, were consistently higher in temperate forests than in subtropical forests. There were considerably different substrate utilization profiles among the boreal, temperate, and subtropical forests. Soil microorganisms from the temperate and boreal forests mainly metabolized high‐energy substrates, while those from the subtropical forests used all substrates equally. In addition, soil Rh rates were significantly and negatively related to soil labile C concentrations, total metabolic activity, and the intensity of individual substrate utilization, indicating that soil microbes assimilated more soil substrates, thereby reducing CO2 emissions. Overall, our study suggests that climate factors, as well as substrate availability, dominate the activities and functions of soil microbes at large scales.